Peran Kantor Urusan Agama (KUA) dalam Mendukung Program Pemberdayaan Ekonomi Badan Amil Zakat Nasional (BAZNAS) Perspektif Ekonomi Syariah (Lembaga Pengembangan Kinerja Dosen, 2026)
Community economic empowerment is the primary goal of Islamic economics, which is directed at achieving prosperity (falah) and distributive justice. Zakat, as an instrument of Islamic economics, plays a strategic role in improving the welfare of mustahik through an economic empowerment program managed by the National Zakat Agency (BAZNAS). Optimizing this program requires synergy with other institutions that have direct contact with the community. The Office of Religious Affairs (KUA), as a technical implementing unit of the Ministry of Religious Affairs at the sub-district level, has strategic potential in supporting the implementation of BAZNAS's economic empowerment program. This study aims to analyze the role of KUA in supporting BAZNAS's economic empowerment program and review it from a sharia economic perspective. This study uses a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation involving KUA staff, BAZNAS managers, and mustahik. The results show that KUA plays a role in zakat socialization, mustahik data collection, and family economic assistance. Viewed from a sharia economic perspective, the role of KUA is in line with the principles of justice, trustworthiness, and maqashid sharia.